A new vision about the influence of major stock markets in CEEC indices: a bidirectional dynamic analysis using transfer entropy - Ferreira, Paulo; Dionísio, Andreia; Almeida, Dora; Quintino, Derick; Aslam, Faheem (My University, 2022)
This research work aims to understand the dynamics of influence among CEEC stock market indices and between these and the US, German, UK and Chinese indices. Through a nonlinear approach, based on transfer entropy, we find strongly influential relationships between some CEEC indices and the influencing nature of the US index stands out. In addition to the complexity of causality relationships, which has a limited compatibility with purely linear analyses, we also perceive an intensification in the leadership of the big 4 from the first quarter of 2020, which suggests that the pandemic crisis may be a factor for the intensification of influence from Chinese and US indices.
Keywords: Bidirectional influence; Granger causality; Net transfer entropy; Transfer entropy